A socio-linguistic approach to the latin middle ages - Richter, Michael (Studies in church history, 1975)
There are two lights, a greater and a smaller one, that is to say, the wiser men and the less wise; the day signifies the wise men, and the night the uninformed. The greater light illuminates the day, for the wiser men instruct those who are more able. What is Augustine if not a sun in the Church? to whom does he speak if not to the wise? You, however, the priests, knowing less, are the smaller light, you illuminate the night, for you preside over the laity who do not know the Scripture and remain in the darkness of ignorance ... The other section of the clergy who do not preside over the people of God are the stars, because although they cannot shine by doctrine, do nevertheless shine by their work onto the earth, that is, the Church.These sentences are taken from an anonymous sermon ‘On the Priesthood’, based on Genesis i, 16-20. The author of the sermon showed the priests their place in society: even though they did not belong to the intellectual elite, their profession and knowledge separated them clearly from the darkness of night in which the laity was imprisoned. In the course of the twelfth century, this passage from Genesis underwent an exegetical change and was used, from then onwards, to explain the political relationship between regnum and sacerdotium. What did remain was the notion of a fundamental difference between clergy and laity, and nowhere was this notion better expressed than in our sermon to the priests: quodcunque lumen estis, lumen estis tamen. In true medieval fashion, our author equated knowledge with the knowledge of the Word of God. He also stressed the fundamental difference between light and darkness, between the clergy and the laity. While theology emphasises that ordination makes the clergy by virtue of its office into the mediator between God and man, this was not the main concern of our author. Instead, he voiced the belief, widely shared by the clergy generally, that knowledge as such was the prerogative of the clergy. Such an attitude raises the question of how the clergy was able to achieve monopoly of knowledge, and how it reacted to attempts by the laity to challenge this monopoly. In what follows I propose to enquire into this phenomenon by looking at the linguistic scene in the medieval west.